Risk factors and predictors of contralateral hip fracture after surgical treatment in elderly patients - Yang, Huan; Yuan, Yusong; Ge, Ruidong; Shi, Lei; Si, Fangda; Chen, Ying (Frontiers in Aging, 2025)
BackgroundHip fractures are common in elderly patients, with some experiencing contralateral fractures. Even so, information on predictors of hip fractures in elderly adults is lacking. In this study, we investigated risk factors for contralateral hip fractures after surgical treatment of primary fractures.MethodsThis was a prospective cohort study of 115 patients aged ≥65 years with low-energy hip fractures. The clinical parameters evaluated included age, sex, bone mineral density (BMD), T score, and hip flexor strength deficit. Patients were stratified into two groups: those with (n = 12) and those without contralateral fractures (n = 103).ResultsContralateral fractures occurred in 10.4% of the patients. Logistic regression revealed that age (OR = 1.08), reduced BMD (OR = 0.33), lower T score (OR = 1.45), and hip flexor imbalance (OR = 2.2) were significant predictors.ConclusionA multimodal approach that integrates anti-osteoporosis therapy and targeted rehabilitation may reduce contralateral fracture risk in elderly patients.